INTEGRATED MANAGEMENT SYSTEMS IMPROVEMENT FOR PRODUCTION ENTERPRISES SUSTAINABLE DEVELOPMENT AND ACHIEVING A SUSTAINABLE SUCCESS: INTEGRATED MANAGEMENT SYSTEMS IMPROVEMENT FOR PRODUCTION ENTERPRISES SUSTAINABLE DEVELOPMENT AND ACHIEVING A SUSTAINABLE SUCCESS - Krachunov, Hristo; Kindzhakova, Elena (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Situation analysis is made before the current study. Staging is described and target of the research problem is determined. Common structure and principles for designing and implementing integrated management systems (IMS) are given. Information base of integrated systems for sustainable development (SD) and environmental protection (EP) in manufacturing plants is briefly described. Two main groups of IMS elements are differentiated - basic and upgrading. Models of IMS are graphically represented. Modeling of production systems for achieving sustainable success (SS) by applying the principles of sustainable development (SD) is presented. Information flows for appro-placement and logistics processes are formed. Indexes and indicators for evaluation of activities for achieving sustainable success are defined. Scientific applied results are synthesized. Findings and conclusions are made.